2019
DOI: 10.22201/iiec.20078951e.2019.198.67411
|View full text |Cite
|
Sign up to set email alerts
|

Broadband adoption in Latin American countries: does geographic proximity matter?

Abstract: This paper analyzes whether geographic proximity among countries can be a significant factor in explaining fixed and mobile broadband adoption in Latin America. To address the research question if neighbor effects could impact on the broadband penetration of a country, we estimate a Spatial Durbin panel data model over the period 2011-2015, for 18 Latin American countries. Results obtained suggest a significant spatial effect of the broadband penetration. In particular, results show positive spatial effects fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(64 reference statements)
0
4
0
3
Order By: Relevance
“…Taking into account the thesis [25], Design of a transport network over fiber optics to increase the broadband of the regions: Arequipa, Moquegua, Puno and Tacna, where he proposes the solution of enabling broadband, speeds higher than 256 kbit/s [26], on an existing overhead electrical network infrastructure, considering that the aforementioned regions are located in rugged geographical areas, areas with difficult to access and extreme climates, factors such as mechanical loads and electrical fields are not considered, which if they are considered as a fundamental part in the present research work, given that when transmitting high information capacity the installed or installed fiber optic has to overcome all geographical and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the thesis [25], Design of a transport network over fiber optics to increase the broadband of the regions: Arequipa, Moquegua, Puno and Tacna, where he proposes the solution of enabling broadband, speeds higher than 256 kbit/s [26], on an existing overhead electrical network infrastructure, considering that the aforementioned regions are located in rugged geographical areas, areas with difficult to access and extreme climates, factors such as mechanical loads and electrical fields are not considered, which if they are considered as a fundamental part in the present research work, given that when transmitting high information capacity the installed or installed fiber optic has to overcome all geographical and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one last enabling factor is that analysts continue to forecast an increase in mobile broadband services (Lugo and Schurmann 2012 ). So far, Alderete ( 2019 ) has reported that mobile broadband penetration growth in Latin American countries has increased on average from 8.27% in 2011 to 44% in 2015.…”
Section: Factors Influencing Networked Learning In Latin Americamentioning
confidence: 99%
“…Sin embargo, en los últimos años ha crecido el interés por el impacto que tienen las tecnologías TICs sobre el crecimiento económico de los países en desarrollo (Achimugu, et al, 2009).En este contexto, muchos estudios han demostrado la influencia directa de las TICs en la eficiencia de la economía a través de su adopción por parte de las empresas locales (Pradhan et al, 2015;Papaioannou & Dimelis 2007) y de las corporaciones internacionales que instalan y emplean dichas tecnologías en los países en desarrollo para sincronizar su actividad productiva a escala global (Narula, 2016;Achimugu et al 2009;Osei-Bryson & Bailey, 2019). Tan importante como la posible interrelación entre las TICs y los factores productivos de un territorio resulta relevante comprender la influencia que ejerce la penetración de la banda ancha móvil en el crecimiento económico de los países en desarrollo; dado que según algunos autores (Alderete, 2019;Katz & Callorda, 2015;Kpodar & Andrianaivo, 2011;Abraham, 2007) este tipo de tecnología está aumentando a un ritmo exponencial en las economías en vías de desarrollo.…”
Section: Aparato Teóricounclassified
“…Hoy, uno de los principales obstáculos a la expansión de los servicios avanzados de comunicaciones en los países en desarrollo, sigue siendo el elevado coste de las telecomunicaciones (Rodríguez, 2005;Adeleye & Aboagu, 2019), lo que dificulta la expansión de las TICs y el crecimiento económico de los países. Si bien, en los últimos años, el uso de móviles con banda ancha han solucionado en parte las dificultades que tenía la difusión de las TICs en este tipo de países (Alderete, 2019).…”
Section: Aparato Teóricounclassified